Learning Islamic Education in Children With Special Needs - Widyastri, Sri; Iskandar, Isman (NOURA: Jurnal Kajian Gender dan Anak, 2024)
The Government regulation states that education can be accessed by all students regardless of background, physical condition, ethnicity, race, and religion. However, in reality, there is still minimal access for students, especially children with special needs, to Islamic education. This article aims to further explore the phenomenon of the process of teaching Islamic Religious Education to children with special needs. This research uses a qualitative research method (field research) with a data collection process through interviews with Nur Asih Ciputat Special School teachers, and the surrounding community as well as direct observation of the learning process and documentation. The theory used in this research is theories of inclusive education which integrates with the theory of society (Luhman 1995). The results of the research show that learning Islamic religious education for students with special needs at the Nur Asih Special School is supported by the idea of ​​exclusion from the surrounding community. The community provides important information and messages as an institution that provides Islamic educational values ​​to children with special needs. Community Involvement is a phenomenon that occurs in the lives of students with special needs in Islamic education teaching. Students can communicate freely and participate in society to experience learning Islamic education from the environment.